SISTEM KEAMANAN OTENTIKASI USER DENGAN NOTIFIKASI REALTIME MELALUI TELEGRAM BERBASIS DALORADIUS - I Nyoman Buda Hartawan; Alfin Zidny Mandela (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2022)
The use of wireless network technology is rapidly increasing at this time causing problems in the security system. Ease of internet access through a wireless network, is also a security hole in the user authentication process. Various smart devices can be used to connect with only one account via the captive portal. In this research, a security system is designed to authenticate hotspot users with daloRADIUS-based telegram notifications. This system integrates hotspot routers, daloRADIUS servers and telegrams to improve the security system during the authentication process. Users are able to monitor the accounts they have used by any device. If there is a suspicious device, the user can also disconnect the device that uses his account to connect to the internet via the telegram application in realtime. Testing is done using the blackbox method by testing the ability of the system to carry out its functions. The test results show that the system is able to function properly and the user can control the use of the hotspot account that is owned through the telegram application in realtime